The importance of HPV DNA test in the screening of cervical cancer [Servıks kanserı taramasinda HPV DNA testının yerı] - (:unkn) unknown (Gunes Kitap Kirtasiye, 2015)
HPV is the most important factor in etiology of the cervical cancer. HPV is the only infectious agent that is highestly associated with a cancer in humans. Thus HPV-DNA is identifed as positive in most squamous cell cervical cancer. That is why HPV DNA test takes an important part of the screening of cervical cancer. Cervical cancer screening programs leads to decrease the incidence of the cervical cancer in the world. Up to now the most commonly used screening test was pap test. However in the last years high effective and useful tests are planning to be developed in addition to these test methods even alone or combined with the HPV-DNA test. © 2015, Gunes Kitap Kirtasiye. All rights reserved.
Keywords: Cancer screening; Cervical cancer; HPV DNA tests